Gender - Based Segregation Class in Madrasah Tsanawiyah - Alfin Husniyah; Septiana Purwaningrum (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
Recently, the intercourse among students is considered to have grown more freely, even it is prevented with various efforts. On the other hand, some experts claim that pesantren(Islamic boarding school) is the best educational system to be apply on withstudentssex-based separation as one of its main characteristic. The system is better known as gender-based segregation. Mostly, it is still implemented in pesantren or private school. Meanwhile, MTs Negeri 1 Kota Blitar, a reputable school in the city, is a state education institution (tied by the government rules) which implements the gender-based class segregation system. The school explains that the system has shown positive impacts in monitoring and reducing the possibilities of the intercourse bad effects among their students. This study applies qualitative approach with case study as its research design. It is aimed to investigate the history, the form and the implications of gender-based class segregation in MTs Negeri 1Kota Blitar. The result shows that (1) The history background of the gender-based class segregation in MTs Negeri 1 Kota Blitar is to adopt the Islamic rules. (2) It implements by separating the classes between male and female students but still around in one single area. (3) The school has received some positive feedbacks of the system, one of them is the savier intercourse between their students.